TINGKAT KETERAMPILAN DASAR PENCAK SILAT ATLET PERGURUAN TAPAK SUCI MUHAMMADIYAH PANCUR BATU - Londut Pandiangan; Muhammad Isnandar; Liliana Puspa Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of basic pencak silat skills of athletes from Tapak Suci Muhammadiyah Pancur Batu Martial Arts School. This research employed a quantitative descriptive method. The sample consisted of 15 athletes from Tapak Suci Muhammadiyah Pancur Batu. The instrument used was a basic pencak silat skills test covering straight kicks, sidekicks, crescent kicks, and punches. Data were collected through direct skill performance tests and analyzed using descriptive percentage techniques. The results showed that 2 athletes (13.33%) were categorized as very good, 2 athletes (13.33%) as good, 3 athletes (20%) as moderate, 1 athlete (6.66%) as poor, and 7 athletes (46.66%) as very poor. Overall, the basic pencak silat skill level of Tapak Suci Muhammadiyah Pancur Batu athletes falls into the very poor category, with the highest frequency found in this category. These findings indicate the need for improved and more structured training programs focusing on basic pencak silat techniques. Coaches are encouraged to emphasize fundamental skill development to enhance athletes’ performance levels. Future studies may involve larger samples and experimental designs to evaluate the effectiveness of specific training interventions.